Perdamaian Antar Umat Beragama: Studi Takhrij dan Syarah Hadis - Bayus Ayatulloh Tamimi; Hidayatul Fikra; Ahmad Soheh Mukarom; Gustiana Isya Marjani (Gunung Djati Conference Series, 2022)
This study aims to analyze hadiths on peace between religious people. This research uses a qualitative approach that is emphasized on the study of literature through takhrij methods and hadith sharah. The results of this study show that the hadith of Imam Ahmad No. 621 describes this peace of shahih quality based on takhrij fists so that this hadith is accepted and practicable. The sharah of this hadith explains that a group of Muslims split apart when Ali made a peace treaty with Muawiyah. The group even considered Ali to have come out of the Qur'an and Sunnah. To restore the situation, Ali sent Abdullah bin Abbas to them so that they would return to the truth. The conclusion of this study is that in any dispute if there is a desire from the disputing parties to make peace it can be done by sending representatives to consult, then make a fair agreement. The study recommends further research on other hadiths on dispute resolution in order to achieve peace, in Muslims in particular and with other religious people in general.